Professional level of the Instructors Working in Gyms of the city of Santa Cruz, Bolivia (Revista horizonte, 2021)
The Ministry of Health of the Plurinational Government of Bolivia (2016), promotes health education, to modify behaviors and attitudes that harm the lives of people. In this context, professionals linked to physical education and physical activity play a fundamental role since they are in charge of planning educational sessions both in educational establishments and in gyms.Objective: Analyze the professional level of instructors working in gyms in the city of Santa Cruz de la Sierra. Method: quantitative research supported by the descriptive statistics of a cross-sectional analysis. The sample was of 115 Instructors (92 men, 23 ladies), of 42 gyms.Results: 14.78% are professionals in the area of Education and / or Physical Activity and sport and 85.22% are not professionals of the area or are from other areas redistributed in the following way; 11.30% in Financial Sciences, 9.57% in Medical Sciences, 6.96% Social Sciences, 11.30% Engineering and, 60.87% in others or do not have any academic training. Conclusions: The results obtained show us a low percentage of professionals trained academically in the area and therefore there is an illegal exercise of the profession and a clear intrusion and professional invasion.